2021
DOI: 10.1210/endocr/bqab042
|View full text |Cite
|
Sign up to set email alerts
|

An Unanticipated Role for Sphingosine Kinase-2 in Bone and in the Anabolic Effect of Parathyroid Hormone

Abstract: Sphingosine-1-phosphate (S1P) is an anabolic clastokine. SPHK is the rate-limiting enzyme in S1P production and has two isoforms. To evaluate the roles of SPHK1 and SPHK2 in bone, we examined the skeletal phenotype of mice with selective deletion of SPHK1 in osteoclasts (SPHK1-Oc -/-) and mice in which the SPHK2 gene was deleted in all tissues (SPHK2 -/-). SPHK1-Oc -/- had normal bone mass. By contrast, SPHK2 -/- female mice had a 14% lower spinal BMD (p<0.01) and males a 22% lower BMD at the same site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Indeed, our data would support this with the increased expression of Sphk2 in murine osteoclasts upon differentiation. Surprisingly, Sphk2 −/− osteoclasts exhibited normal resorptive activity in vitro, despite global Sphk2 −/− mice showing reduced trabecular bone mass [23]. It could be argued that the in vivo phenotype is due to the importance of Sphk2 osteoblast function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our data would support this with the increased expression of Sphk2 in murine osteoclasts upon differentiation. Surprisingly, Sphk2 −/− osteoclasts exhibited normal resorptive activity in vitro, despite global Sphk2 −/− mice showing reduced trabecular bone mass [23]. It could be argued that the in vivo phenotype is due to the importance of Sphk2 osteoblast function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, alterations in SPHK1 expression during osteoblast differentiation have been linked to the activation of S1PR1 signalling [ 23 ]. To the best of our knowledge, no studies have investigated the impact of intracellular osteoblastic SPHK1 and/or S1P signalling; however, it has been shown that the osteoclast-specific deletion of SPHK1 has no effect on bone mass in male or female mice [ 26 ]. Similarly, siRNA knockdown of SPHK1 in a murine macrophage cell line (RAW264) or in primary murine bone-marrow-derived macrophages had no effect on osteoclast maturation in response to RANKL [ 24 ].…”
Section: S1p Signallingmentioning
confidence: 99%
“…The inhibition of SPHK2 in the murine macrophage cell line RAW264 resulted in a reduction in c-FOS expression and subsequent osteoclastogenesis [ 27 ], identifying intracellular SPHK2 signalling as essential during the initial stages of osteoclastogenesis. In contrast, SPHK2 −/− osteoclasts had normal resorptive activity in vitro, despite the observation that global SPHK2 −/− mice have reduced trabecular bone mass [ 26 ]. This finding led to the in vivo phenotype being attributed to alterations in osteoblast formation, which was demonstrated by a reduction in collagen 1 gene expression and a significant impairment of the anabolic response to PTH within these mice [ 26 ].…”
Section: S1p Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of cancer cells has been reported to be suppressed when both the SK isotypes are inhibited. These isotypes are known to act by being located in different parts of the cell [ 7 , 8 , 9 ]. S1P generation, according to the location of SK1 and SK2, plays an important role in inducing the survival of cancer cells in specific oncogenic signaling pathways [ 10 ].…”
Section: Introductionmentioning
confidence: 99%